2020
DOI: 10.1097/aog.0000000000003983
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Universal Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) Testing in Pregnancy

Abstract: The data in this report reflect events and activities as of April 4, 2020 at 05:00 PM. All data in this report are preliminary and subject to change as cases continue to be investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 43 publications
(39 citation statements)
references
References 2 publications
2
35
1
1
Order By: Relevance
“…On the other side, reports by Naqvi et al [25] and Gagliardi et al [12], reported a low performance of universal screening based either on an overall lower disease burden in their region or due to a referred "steady state" of virus circulation, with less than 1% of asymptomatic confirmed cases. In an intermediate epidemiological situation [24] reports by Khalil et al [11], Miller et al [14] and Ochiai et al [26] presented observed SARS-CoV-2 infection prevalence ranging between 3 and 7%, with up to 6% of asymptomatic confirmed cases among screened population, which are similar to our findings. In our study, at the moment of the initial recruitment, according to the official data reported by the National Ministry of Health, there were about 7858 confirmed cases of SARS CoV-2 in the city of Santiago, with a cumulative incidence of 96.7 per 100000 habitants.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 92%
See 2 more Smart Citations
“…On the other side, reports by Naqvi et al [25] and Gagliardi et al [12], reported a low performance of universal screening based either on an overall lower disease burden in their region or due to a referred "steady state" of virus circulation, with less than 1% of asymptomatic confirmed cases. In an intermediate epidemiological situation [24] reports by Khalil et al [11], Miller et al [14] and Ochiai et al [26] presented observed SARS-CoV-2 infection prevalence ranging between 3 and 7%, with up to 6% of asymptomatic confirmed cases among screened population, which are similar to our findings. In our study, at the moment of the initial recruitment, according to the official data reported by the National Ministry of Health, there were about 7858 confirmed cases of SARS CoV-2 in the city of Santiago, with a cumulative incidence of 96.7 per 100000 habitants.…”
Section: Results In the Context Of What Is Knownsupporting
confidence: 92%
“…Two-sided p-values of less than 0.05 were considered statistically significant. The statistical package used for analysis was Stata v. 14…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…symptoms, such as loss of smell or taste, may also have played an important role [3,29]. Olfactory and taste disorders have been reported as the only symptoms of infection in up to 17% of SARS-CoV-2 positive individuals, and to display a higher predictive ability of having the virus than fever or persistent cough [16,18,19].…”
Section: Plos Onementioning
confidence: 99%
“…Universal screening by reverse transcription-polymerase chain reaction (RT-PCR) of nasopharyngeal swabs has been proposed as the optimal approach [3][4][5][6]. However, limited testing supplies and laboratory workforce may prevent its application in some clinical settings [7].…”
Section: Introductionmentioning
confidence: 99%